Prognostic factors and survival outcomes in patients with chronic myeloid leukemia in blast phase in the tyrosine kinase inhibitor era: Cohort study of 477 patients. Issue 22 (25th July 2017) - Jain, Preetesh; Kantarjian, Hagop M.; Ghorab, Ahmad; Sasaki, Koji; Jabbour, Elias J.; Nogueras Gonzalez, Graciela; Kanagal‐Shamanna, Rashmi; Issa, Ghayas C.; Garcia‐Manero, Guillermo; KC, Devendra; Dellasala, Sara; Pierce, Sherry; et al.
Abstract : BACKGROUND: Outcomes in patients with chronic myeloid leukemia in blast phase (CML‐BP) are historically dismal. Herein, the authors sought to analyze the characteristics, prognostic factors, and survival outcomes in patients with CML‐BP in the tyrosine kinase inhibitor (TKI) era. METHODS: A total of 477 patients with CML‐BP were treated with a TKI at some point during the course of their CML. Cox proportional hazard models identified characteristics that were predictive of survival. Overall survival and failure‐free survival were assessed. Optimal cutoff points for specific parameters were identified using classification and regression tree (CART) analysis. RESULTS: The median age of the patients was 53 years (range, 16‐84 years) and 64% were male. Approximately 80% of patients initially were diagnosed in the chronic phase of CML at a median of 41 months (range, 0.7‐298 months) before transformation to CML‐BP. De novo CML‐BP occurred in 71 patients. Approximately 72% of patients received TKI therapy before CML‐BP. The initial therapy for CML‐BP included a TKI alone (35%), a TKI with chemotherapy (46%), and non‐TKI therapies (19%). The median overall survival was 12 months and the median failure‐free survival was 5 months. In multivariate analysis, myeloid immunophenotype, prior TKI, age ≥58 years, lactate dehydrogenase level ≥1227 IU/L, platelet count < 102 K/μL, no history of stem cell transplantation, transition to BP from chronic phase/accelerated phase, and the presence of chromosome 15 aberrations predicted for a significantly increased risk of death. Achievement of major hematologic response and/or complete cytogenetic response to first‐line treatment was found to be predictive of better survival. The combination of a TKI with intensive chemotherapy followed by stem cell transplantation appeared to confer the best outcome. CONCLUSIONS: Patients with CML‐BP continue to pose a therapeutic challenge, have dismal outcomes, and require newer treatment approaches. Cancer 2017;123:4391‐402 . © 2017 American Cancer Society . Abstract : In the current study, myeloid immunophenotype, prior treatment with tyrosine kinase inhibitors (TKIs), older age, higher lactate dehydrogenase level, low platelet count, stem cell transplantation after blast phase (BP) diagnosis, chronic myeloid leukemia (CML) transformed from chronic phase/accelerated phase, and the presence of chromosome 15 abnormalities are found to be predictive of poor survival in patients with CML‐BP. Patients with CML‐BP who are treated with a combination of a TKI with chemotherapy appear to have superior survival compared with patients treated with a TKI alone.